New, Useful Criteria for Assessing the Evidence of Infection in Sepsis Research. (17th May 2022) - Mellhammar, Lisa; Elén, Sixten; Ehrhard, Simone; Bouma, Hjalmar; Ninck, Lorenz; Muntjewerff, Eva; Wünsch, Daniel; Bloos, Frank; Malmström, Erik; Linder, Adam
Abstract : OBJECTIVES: The Sepsis-3 definition states the clinical criteria for sepsis but lacks clear definitions of the underlying infection. To address the lack of applicable definitions of infection for sepsis research, we propose new criteria, termed the Linder-Mellhammar criteria of infection (LMCI). The aim of this study was to validate these new infection criteria. DESIGN: A multicenter cohort study of patients with suspected infection who were admitted to emergency departments or ICUs. Data were collected from medical records and from study investigators. SETTING: Four academic hospitals in Sweden, Switzerland, the Netherlands, and Germany. PATIENTS: A total of 934 adult patients with suspected infection or suspected sepsis. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Agreement of infection site classification was measured using the LMCI with Cohen κ coefficient, compared with the Calandra and Cohen definitions of infection and diagnosis on hospital discharge as references. In one of the cohorts, comparisons were also made to adjudications by an expert panel. A subset of patients was assessed for interobserver agreement. MEASUREMENTS AND MAIN RESULTS: The precision of the LMCI varied according to the applied reference. LMCI performed better than the Calandra and Cohen definitions (κ = 0.62 [95% CI, 0.59–0.65] vs κ = 0.43 [95% CI, 0.39–0.47], respectively) and the diagnosis on hospital discharge (κ = 0.57 [95% CI, 0.53–0.61] vs κ = 0.43 [95% CI, 0.39–0.47], respectively). The interobserver agreement for the LMCI was evaluated in 91 patients, with agreement in 77%, κ = 0.72 (95% CI, 0.60–0.85). When tested with adjudication as the gold standard, the LMCI still outperformed the Calandra and Cohen definitions (κ = 0.65 [95% CI, 0.60–0.70] vs κ = 0.29 [95% CI, 0.24–0.33], respectively). CONCLUSIONS: The LMCI is useful criterion of infection that is intended for sepsis research, in and outside of the ICU. Useful criteria for infection have the potential to facilitate more comparable sepsis research and exclude sepsis mimics from clinical studies, thus improving and simplifying sepsis research.